STRATEGI OPTIMALISASI DANA WAKAF: PEMERATAAN DANA WAKAF SELAMA PANDEMI - Laila M Pimada; Rizqi Bhakti Nur Sayuta; Echa Valentina Gunawan (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
This study aims to provide suggestions and strategies based on theoretical concepts and the latest phenomena that occur in order to optimize the distribution of waqf funds in the Covid-19 pandemic era to internal and external parties in the sustainability of waqf in Indonesia. This study uses a qualitative approach to the study of literature by using books and literature as research objects. The results of this study was found in 19 scientific journals consisting of the topic Existing Conditions of Waqf Management in Indonesia which focus on data on the potential of waqf, Waqf Literacy as an Effort to Optimize the Role of Waqf, Optimization of Waqf in the Health Sector, Optimization of Waqf in the Microeconomic Sector, and Optimization of Waqf in the Social Sector. The  entire research paper ids devided into five discussion topics, each of which produces suggestions and strategies for three sectors, namely the government, nadzhir waqf, and further research.